Fluid polarity shifts initiate and amplify preferential flow in clay-rich media - Peihao Ouyang; Shijin Feng; He Chen; Qiteng Zheng; Xiaolei Zhang (Proceedings of the National Academy of Sciences, 2026)
Preferential flow governs fluid and solute transport across scales from micropores to regional watersheds, yet it is commonly attributed to static pore-structure heterogeneity. Here, we show that fluid polarity can actively reorganize pore networks and amplify preferential flow in kaolinite-rich clay media. In permeation experiments, replacing water with a low-polar hydrofluoroether triggers early breakthrough (~0.4 d) and permeability up to ~62.7× higher than predicted by standard relative permeability functions at only 18.8% low-polar saturation. Multiscale imaging and porosimetry show a transition from unimodal microporosity to connected pore-fracture bimodal architectures. Interfacial measurements indicate that low-polar fluids weaken interparticle electrostatic repulsion and thereby reorganize pore space by reducing ineffective pores and activating latent connectivity. Guided by the cross-scale mechanistic chain, we establish a one-parameter relationship linking interfacial forces to ineffective porosity and integrate it into a coupled framework that reproduces preferential path development and permeability evolution across 21 clay-rich media and 24 fluids. These findings advance a cross-scale framework for polarity-driven transport dynamics and provide a basis for incorporating fluid polarity into predictive subsurface transport models in shallow clay-rich environments.